Reproductive Performance of The Female Peranakan Ettawa in Tandebura Village - I Made Budianto; H. Hastuti; H. Husnaeni (Chalaza Journal of Animal Husbandry, 2019)
This research aims to know the performance of the reproduction of a female Peranakan Ettawa that is held in Tandebura village. This research was conducted in October to November 2018 in Tandebura subdistrict Watubangga District Kolaka Regency. Population Data of goat's cattle Ettawa (PE) is obtained from direct observation and Resort Livestock Village The Tandebura. Subsequent data is treated descriptively using the CR and NRR formulas followed by correlation analysis.  The observed variables are the Conception Rate (CR0 and the Non-Return Rate (NRR).  The results of the study showed the success of natural wedding in Tandebura sub-district Watubangga Kolaka District is a good value of CR (76.05%) and the NRR (83.09%).  The amount of the collapse of CR-NRR + 1, can be concluded that the success of the natural Wedding Goat breeds Ettawa (PE) females with the number of goat cattle PE as much as 71 tails in the category of right according to the CR and NRR standards and have a solid coloration.